Minimizing impacts of climate change on coastal aquatic resources through the integrated mariculture - Rahman, Mohammad Mustafizur; Yunus, Kamaruzzaman; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal (2011)
Climate change is a critical issue nowadays. Various anthropogenic activities are making the world hot to hotter. The ultimate result is global climate change, which has been reached to an alarming level especially in the marine environment. Climate change represents several factors associated with increasing atmospheric concentrations of greenhouse gases. These include increasing sea temperatures, increasing acidification of the oceans, increasing sea level and related factors such as storms and precipitation patterns. Beside the factors related to climate change, non-climate stresses such as harvesting, contaminants, non-native species introductions, habitat and coastal zone modifications and changes in nutrient additions are also important. Non-climate stresses on marine ecosystems are mostly related to some intensive coastal aquaculture practices. Non-climate related stresses together with climate change tresses, have been adversely linked to both direct and indirect effects on fisheries and aquaculture productions as well as aquatic resources. CO2 emission is progressively increasing resulting in pH decline in marine environments. The pH decline then decreases the availability of chemical building blocks needed by organisms that produce shells and skeletons. Therefore, sequestration of CO2 from the marine environments is today’s demand in order to reduce the impact of CO2 on marine aquatic resources. Seaweeds are highly efficient in removing CO2 and nitrogenous and phosphorous nutrients from marine water. Besides CO2 sequestration, seaweed cultivation has a great importance in meeting to some extent global food, fodder, fuel and pharmaceutical requirements. Filter-feeding bivalves also efficiently utilize oceanic carbon to generate their shell. Filter-feeding bivalves consume organic particulates and directly lower the extent of organic pollution. Therefore, integrated aquaculture with seaweed and fish or seaweed and shellfish or seaweed, shellfish and fish can be proposed to develop environmentally sound aquaculture practices through a balance ecosystem approach to avoid pronounced shifts in coastal processes.